Evidence that histamine and carbachol may open the same ion channels in longitudinal smooth muscle of guinea-pig ileum - Bolton, T. B. (1981)
1. Membrane potential was recorded intracellularly by micro-electrode in separated longitudinal muscle of guinea-pig ileum. Electrotonic potentials were evoked in longitudinal strips by passing current between large external electrodes in the partition chamber. 2. Histamine increased the frequency of action potential discharge at low concentrations and depolarized the membrane. At higher concentrations it caused substantial depolarization and action potential discharge was abolished. Carbachol had similar actions but the maximal depolarization by carbachol (using 10(-4) m) was some 4-5 mV greater than maximal depolarization by histamine (using 10(-4) m). 3. The change in size of evoked electrotonic potentials was used to estimate the effects of carbachol and histamine on the conductance of the smooth muscle membrane. The equilibrium potentials for histamine and carbachol depolarizations were estimated from their relative effects on potential and conductance and were found to be not significantly different; measurements of the effects on conductance showed that 10(-4) m-histamine increased conductance about 8-fold whilst 10(-4) m-carbachol had a much greater effect on conductance. This difference could explain the differing maximal depolarizing effects of these agents if both were assumed to open channels having the same ionic selectivity (i.e. equilibrium potential). 4. The efflux of (42)K was studied in separated strips of longitudinal ileal muscle from guinea-pig. In the presence of a concentration of carbachol (2 × 10(-5) m or 10(-4) m) having a maximal effect on (42)K efflux rate, histamine (10(-4) m) did not increase efflux further although 120 mm-potassium did so. Experiments with the irreversible muscarinic receptor blocker, propylbenzilylcholine mustard, indicated that the number of muscarinic receptors did not limit the (42)K efflux response to carbachol and it was suggested that the response was limited by the availability of ion channels which could be opened by activated muscarinic receptors. 5. Contractions to histamine and carbachol in 120 mm-potassium depolarizing solution were followed upon washing by a relaxation below basal tension. Carbachol, but not histamine, showed a pronounced and long lasting secondary contraction following this relaxation. 6. These results are consistent with the idea that activated histamine and activated muscarinic receptors open the same ion channels in the smooth muscle membrane to produce depolarization, increased action potential discharge and contraction, although muscarinic receptors can open more of these. However, there was evidence that the opening of these channels is not the only pathway between receptor activation and contraction.